Toxic metals and metalloids: Uptake, transport, detoxification, phytoremediation, and crop improvement for safer food - Zhao, Fang-Jie; Tang, Zhong; Song, Jia-Jun; Huang, Xin-Yuan; Wang, Peng (Molecular plant, 2022)
Agricultural soils are under threat of toxic metal/metalloid contamination from anthropogenic activities, leading to excessive accumulation of arsenic (As), cadmium (Cd), lead (Pb), and mercury (Hg) in food crops that poses significant risks to human health. Understanding how these toxic metals and their methylated species are taken up, translocated, and detoxified is prerequisite to developing strategies to limit their accumulation for safer food. Toxic metals are taken up and transported across different cellular compartments and plant tissues via various transporters for essential or beneficial nutrients, e.g. As by phosphate and silicon transporters, and Cd by manganese (Mn), zinc (Zn), and iron (Fe) transporters. These transport processes are subjected to interactions with nutrients and the regulation at the transcriptional and post-translational levels. Complexation with thiol-rich compounds, such as phytochelatins, and sequestration in the vacuoles are the common mechanisms for detoxification and for limiting their translocation. A number of genes involved in toxic metal uptake, transport, and detoxification have been identified, offering targets for genetic manipulation via gene editing or transgenic technologies. Natural variations in toxic metal accumulation exist within crop germplasm, and some of the quantitative trait loci underlying these variations have been cloned, paving the way for marker-assisted breeding of low metal accumulation crops. Using plants to extract and remove toxic metals from soil is also possible, but this phytoremediation approach requires metal hyperaccumulation for efficiency. Knowledge gaps and future research needs are also discussed. Accumulation of toxic metals and metalloids, such as arsenic, cadmium, lead, and mercury in food crops, can affect food safety and human health. This review discusses the molecular mechanisms and regulation of their uptake, transport, and detoxification as well as crop improvement strategies to reduce their accumulation in the edible parts. The potential of using metal-accumulating plants to clean up contaminated soil is also discussed.